The impact of corporate turbulence on: Managers' attitudes - Reilly, Anne H.; Brett, Jeanne M.; Stroh, Linda K. (Strategic Management Journal, 1993)
This cross-level study tested the relationship between organizational turbulence as reported by 49 strategic business unit managers from 17 Fortune 500 companies and the attitudes of 679 midlevel managers in these companies. The results indicated that turbulence clustered into four dimensions that were differentially related to managers' attitudes. Incremental negative turbulence was negatively associated with satisfaction with job security. Financial restructuring was positively associated with career loyalty. Growth was positively associated with career loyalty and with job involvement. Organizational breakup was positively associated with career loyalty. The long-term implications for companies of the career-loyallcompany-loyal, job-involved but job-insecure management cadre produced by the corporate turbulence of the 1980s are discussed.